PARTICULARITIES OF TRAINING AT THE THEMATIC CYCLE "TUBERCULOSIS: MEDICAL AND PHARMACEUTICAL ASSISTANCE, LEGAL SUPPORT" FOR GENERAL PRACTITIONERS-FAMILY DOCTORS - Shapovalov Валерій; Shapovalov Валентин; Shapovalova Вікторія; Osyntseva Аліна; Nehretskii Сергій; Derkach Анатолій (Actual Problems of Medicine and Pharmacy, 2023)
Proven that one of the main threats to human health at the present stage are infectious diseases, in particular tuberculosis. The growth of the role of improving the qualifications of family doctors in the cycles of thematic improvement regarding medical and pharmaceutical care for patients with tuberculosis in the system of continuous postgraduate development was substantiated. The educational and methodological design of the thematic cycle "Tuberculosis: medical and pharmaceutical assistance, legal support" for general practitioners, family doctors using distance learning technologies (Viber, Zoom, Google Classroom, Google Workspace, etc.) was developed.